EXPLORING TIKTOK FOR ENHANCING SECONDARY SCHOOL STUDENTS' UNDERSTANDING OF LEARNING GRAMMAR: A QUALITATIVE STUDY - Rachmawati, Yuliana; Rohmah, St. Shabibatul (STKIP PGRI Situbondo, 2025)
Linguistic proficiency in grammar constitutes a critical element of communicative competence, enabling precise and nuanced verbal expression. Consequently, grammar learning within Indonesian educational frameworks represents a pivotal pedagogical objective integrated into curricular design for secondary school students, particularly through qualitative approaches in educational technology and social media phenomenon study. However, there are still many intermediate students who still have difficulty understand learning grammar. TikTok is the solution to become a grammar learning preference, almost all students use TikTok. The research uses qualitative methods that focus on the study of phenomena. Data collection uses observation, reflective journals, interviews, and document analysis. The findings reveal that students perceive TikTok as a highly engaging and enjoyable medium for learning grammar. The platform's short, visually appealing, and interactive videos enable students to grasp grammatical concepts more effectively in a relaxed and informal environment. Additionally, students reported an increase in motivation and confidence in applying grammar rules in both written and spoken English. These insights suggest that TikTok can serve as a valuable supplementary tool for grammar education, fostering independent learning and improving overall language proficiency in a digital age.